Venous thromboembolism associates with SARS-CoV-2 more than seasonal influenza. Issue 205 (September 2021) - Lachant, Daniel; Roto, Dominick; Rappaport, Stephen; Prasad, Paritosh; Lachant, Neil; White, R. James
Highlights: SARS-CoV-2 is associated with increased venous thromboembolism (VTE) risk. VTE was more commonly seen with SARS-CoV-2 than seasonal influenza. Chronic anticoagulation may decrease VTE risk and disease severity with SARS-CoV-2.